Inovasi model dan pendekatan evaluasi untuk meningkatkan kompetensi siswa MTsN 1 Kota Padang pada pendidikan Islam - Resti Susanti; Syahri Rahmi; Nani Hayda Fitri; Maryani Sastera; Sri Wahyuni (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Assessment is a crucial component in Islamic education, encompassing not only the measurement of students’ knowledge but also their skills and attitudes. This study aims to analyze innovative evaluation models and approaches that can enhance students’ competencies at MTsN 1 Kota Padang. The research employed a quasi-experimental approach with a pretest-posttest design for both experimental and control classes. Research instruments included competency tests, attitude observations, and student portfolios. The results indicate that the implementation of innovative evaluation models, including authentic assessment and portfolios, significantly improves students’ conceptual understanding, practical skills, and religious attitudes compared to conventional evaluation models. These findings underscore the importance of developing holistic, creative, and competency-oriented evaluation approaches in Islamic education. The study also provides recommendations for teachers to systematically integrate innovative evaluation models into the teaching and learning process.